2022
DOI: 10.1590/2175-8239-jbn-2020-0222
|View full text |Cite
|
Sign up to set email alerts
|

Use of non-conventional biomarkers in the early diagnosis of acute kidney injury in preterm newborns with sepsis

Abstract: Acute kidney injury (AKI) is a common finding in Neotatal Intensive Care Units (NICU). Sepsis is one the main causes of AKI in preterm newborns. AKI has been associated with significant death rates. Early detection of the condition is the first step to improving prevention, treatment, and outcomes, while decreasing length of hospitalization, care costs, and morbimortality. AKI may progress to chronic kidney disease (CKD), a condition linked with dialysis and greater risk of cardiovascular disease. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…In a cohort-matched study, Coggins et al reported increased rates of AKI and greater AKI severity in neonates with culture-proven sepsis [53]. The mechanism in which sepsis contributes to the development of AKI may include decreased GFR, renal vasoconstriction, and reduced local blood flow [54].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort-matched study, Coggins et al reported increased rates of AKI and greater AKI severity in neonates with culture-proven sepsis [53]. The mechanism in which sepsis contributes to the development of AKI may include decreased GFR, renal vasoconstriction, and reduced local blood flow [54].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a UTI, which, depending on its severity, can progress to AKI, is the third infectious cause most related to progression to a septic condition, behind lung and abdominal infections [27], triggering the pathophysiological condition described previously [26]. Furthermore, patients who progress with severity may require mechanical ventilation and administration of nephrotoxic drugs, which tend to increase harmful effects on renal function [28], so it is essential to explore new biomarkers, which can allow the application of interventions, evaluate responses to treatment, detect biological abnormalities, and assess the prognosis according to the development of the disease [29]. The 28th Acute Disease Quality Initiative consensus reported that SA-AKI recommends utilizing sepsis biomarkers in conjunction with functional and tubular injury-related biomarkers to enhance the prognosis of early or late SA-AKI [25].…”
Section: The Crosstalk Between Acute Kidney Injury and Sepsismentioning
confidence: 99%
“…Neonatal sepsis is frequently assessed in preterm newborns, secondary to pathogens acquired after birth, and is defined as early (ES) or late (LS) sepsis if diagnosis occurs within or after 72 h of birth, respectively [ 80 ]. Neonatal sepsis is inversely related to birth weight and gestational age, with a high prevalence in very-low-birth-weight neonates [ 81 ] and with gestational age (GA) < 28 weeks [ 82 ].…”
Section: Risk Factors For Aki In Neonatal Intensive Carementioning
confidence: 99%